Teacher Practice in the Secreterial Area: A Decisive Exercise to Minimize University Dropout Rates - Canales García, Alba (2014)
Case study conducted under the qualitative methodology and over the experience developed in the Professional Practice course. We wanted to study the perceptions of students regarding: the relevance of the promoted learning and its correspondence with the learning needs of the students as a key point to minimize the drop-out rate, the value given to the development of knowledge and the implementation of innovation initiatives that motivate students to conclude their university training. It is concluded that professional practice courses must become spaces for the construction of knowledge from which a profile is derived. This profile must meet the demands of significance, autonomy and relevance that contemporary society demands, all this as part of training initiatives aimed to minimized dropout rates in higher education.